Hubungan self acceptance dan Fear Of Missing Out (Fomo) Mahasiswa Generasi Z Pengguna Aplikasi Tiktok - Wardani Putri, Thania Auruly; Budi Hapsari, Maharani Tyas (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2024)
Social media often displays the most pleasant moments from other people's lives that they want to show their followers, but this is often used as a benchmark and compared to negative aspects in a person's life to cause social anxiety or fear of missing out. Self-acceptance is one of the factors that influence the fear of missing out. The uniqueness of this study lies in the variables used, some studies reveal the overall psychological well being without revealing the relationship between aspects of psychological well being with fear of missing out which one aspect is self acceptance, some previous studies focused on the Instagram application and this research focused on the TikTok application which is currently a trending application. The purpose of this study was to determine the relationship between self-acceptance and fear of missing out Gen Z students using the TikTok application. This research method is quantitative correlational using purposive sampling sample selection technique. The population of this study consisted of 106 Gen Z students domiciled in Solo Raya and a sample of 35 respondents. Psychological scale with Likert scale model consisting of self-acceptance scale and fear of missing out scale prepared by modifying existing measuring instruments. Data analysis using product moment correlation technique. Data analysis yielded a correlation coefficient of -0.552 and a sig of 0.000, hence the hypothesis proposed by the researcher was accepted. That is, the self-acceptance of Gen Z students using the TikTok application has a negative relationship with fear of missing out and vice versa. Keywords: Self Acceptance; Generation Z; Fear of Missing Out; TikTok.